Silicotungstic acid as a highly efficient coreactant for luminol chemiluminescence for sensitive detection of uric acid. Issue 7 (20th February 2020) - Mostafa, Islam M.; Halawa, Mohamed Ibrahim; Chen, Yequan; Abdussalam, Abubakar; Guan, Yiran; Xu, Guobao
Abstract : Polyoxometalate has been introduced for the first time as a new coreactant for luminol CL, and it has been utilized for selective and sensitive detection of uric acid. Abstract : Herein, we report luminol–silicotungstic acid (STA) chemiluminescence (CL) for the first time. The luminol–STA system resulted in remarkable CL enhancement (65 times) compared with the known classical luminol–H2 O2 system because of the generation of the strong oxidizing agent tungsten trioxide from STA. Based on the quenching effect of uric acid, the new CL system is applied for the sensitive and selective assay of uric acid in its pure state (LOD 0.75 nM) and in real human urine with excellent recoveries in the range of 99.6–102.3%. Furthermore, this system permits the efficient detection of STA (LOD, 0.24 μM).